PENGARUH MODEL PROJECT BASED LEARNING BERBANTU LEMBAR KERJA PESERTA DIDIK (LKPD) TERHADAP KREATIVITAS SISWA SEKOLAH DASAR - Weny Widya; Ernawati Saptaningrum; Mei Fita Asri Untari (Jurnal Guru Kita PGSD, 2019)
Abstract:The Effect of Project Based Learning Model Assisted Student Worksheet (LKPD) on the Creativity of Elementary School Students. The purpose of this study was to determine whether there is an effect of the Project Based Learning model assisted by student worksheets (LKPD) on the Creativity of Elementary School Students, in the second semester of the 2018/2019 academic year. The subject of this class is the VA class SDN Kalicari 01 Semarang which consists of 13 male students and 17 female students. This type of research is quantitative in the form of Pre Experimental Design with the design of One Group Pretest-Posttest Design. The results of the analysis of the increase using a gain test which has a value of 0.5 with moderate criteria. The average results of the percentage of implementation of the Project Based Leraning model by 95% in the excellent category. This is reinforced by the results of t-test calculations obtained pretest and posttest values obtained t_count = 17.716 t_table = 1,699 db N-1 = 30-1 = 29 with a significant level of 5% so the value of t_ (count)> t_table can therefore be concluded that the Project Based Learning model assisted by the Student Worksheet (LKPD) has an effect on the creativity of elementary school students.Keywords: Project Based Learning, LKPd, CreativityAbstrak: Pengaruh Model Project Based Learning Berbantu Lembar Kerja Peserta Didik (LKPD) terhadap Kreativitas Siswa Sekolah Dasar. Tujuan penelitian ini adalah untuk mengetahui adakah pengaruh model Project Based Learning berbantu lembar kerja peserta didik (LKPD) terhadap Kreativitas Siswa Sekolah Dasar, pada semester II tahun pelajaran 2018/2019. Subjek penelitian kelas ini adalah kelas VA SD N Kalicari 01 Semarang yang terdiri atas 13 siswa laki-laki dan 17 siswa perempuan.Jenis penelitian ini adalah kuantitatif dalam bentuk Pre Experimental Design dengan desain One Grup Pretest-Posttest Design. Hasil analisis peningkatan menggunakan uji gain yang  memiliki nilai sebesar 0,5 dengan kriteria sedang. Hasil rata-rata presentase keterlaksanaan model Project Based Leraning sebesar 95% pada kategori sangat baik. Hal tersebut diperkuat dengan hasil perhitungan uji t yang didapatkan hasil nilai pretest dan posttest diperoleh  db N-1= 30-1=29 dengan taraf signifikan 5% jadi nilai  oleh karena itu dapat disimpulkan bahwa model Project Based Learning berbantu Lembar Kerja Peserta Didik (LKPD) berpengaruh terhadap Kreativitas Siswa Sekolah Dasar.Kata Kunci : Project Based Learning, LKPD, Kreativitas.